Bibliometric analysis of the Spanish scientific production in Optometry - Fernández-Ramos, Andrés; Albaida-Ventura, Anna-María (Revista General de Información y Documentación, 2025)
Optometry is recognized as a health profession, which is gaining great relevance due to the high visual demands required by the new technologies that we use in our daily lives. This study analyzes the scientific production in the area of ​​optometry generated in Spanish institutions. Scopus is used as a data source, including the Spanish publications collected in the journals indexed in the Optometry category and those that have been recovered through the search of the entire database using the descriptor optometr* up to the year 2023 included. Indicators of production, impact and collaboration were obtained and the main topics addressed, the most productive authors and institutions of the 1,107 publications included in the study were analyzed. The results show that Optometry in Spain is at a time of expansion of its scientific production.
Keywords: Spain; Optometry; Scientific production; bibliometric indicators; Scopus